Entrepreneurial Innovations, Entrepreneurship Policy and Globalization - Robin Douhan; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2009)
What explains the world-wide trend of pro-entrepreneurial policies in the last few decades? We study entrepreneurial policy in a lobbying model taking into account the con.ict of interest between entrepreneurs and incumbents. It is shown that international market integration leads to more pro-entrepreneurial policies. It becomes more difficult to protect the profits of incumbent firms from entrepreneurial entry and pro-entrepreneurial policies make foreign entrepreneurs less aggressive. Making use of the Doing Business database, we find, consistent with our theory, evidence that international openness reduces barriers to entry for new entrepreneurs and that the effect is stronger in countries with more rent-seeking governments.
Keywords: D73; F15; L26; L51; O31; 330; Entrepreneurship; Regulation; Innovation; Market Integration; Lobbying; Entrepreneurship-Ansatz; Innovation; Wirtschaftspolitik; Interessenpolitik; Regulierung; Marktintegration; Theorie